Easy estimation of endoglucanase activity using a free software app for mobile devices - Guedes, Wesley Nascimento [UNESP]; Lucena, Guilherme Nunes [UNESP]; de Paula, Ariela Veloso [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Pereira, Fabíola Manhas Verbi [UNESP] (Brazilian Journal of Analytical Chemistry, 2020)
This study describes the estimation of the enzymatic activity of endoglucanase based on the 3,5-dinitrosalicylic acid (DNS) method and carboxymethylcellulose (CMC) substrate using glucose as the analyte. As an alternative to measuring the colored product obtained by the reaction between glucose and DNS, a free software app for mobile devices was used for estimating the color intensity of solutions, replacing the need of a UV-Vis spectrophotometer (reference method). The app is able to convert images in color histograms to red (R), green (G) and blue (B) scales and to provide univariate and multivariate calculations of the image data. The chemometric technique partial least squares (PLS) was employed with the app and presented accurate results that were comparable to those of the reference method. A correlation coefficient of 0.983 was obtained for the linear range between 0.60 and 2.60 mg mL-1 of glucose, and the standard error of cross-validation (SECV) was 0.219 mg mL-1. The proposed method (imaging – PLS) was applied for samples of cellulase enzymes from Aspergillus niger and Trichoderma reesei, revealing an interesting alternative to estimate the enzymatic activity of endoglucanase.
Keywords: Digital imaging; Endoglucanase activity; Free software app; PLS